Assessing Investment and Longevity Risks within Immediate Annuities - Daniel Bauer; Frederik Weber (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2007)
Life annuities provide a guaranteed income for the remainder of the recipient's lifetime, and therefore, annuitization presents an important option when choosing an adequate investment strategy for the retirement ages. While there are numerous research articles studying annuities from a pensioner's point of view, thus far there have been few contributions considering annuities from the provider's perspective. In particular, to date there are no surveys of the general risks within annuity books. The present paper aims at filling this gap: Using a simulation framework, it provides a long-term analysis of the risks within annuity books. In particular, the joint impact of mortality risks and investment risks as well as their respective influences on the insurer's financial situation are studied. The key finding is that, under the model specifications and using annuity data from the United Kingdom, the risk premium charged for aggregate mortality risk seems to be very large relative to its characteristics. Possible reasons as well as economic implications are provided, and potential caveats are discussed.
urn:nbn:de:bvb:19-epub-1982-4
Keywords: C15; G22; G32; 650; Annuities; Lee-Carter Model; Longevity Risk